Oxidative profiles of endurance horses racing different distances - R.F. Siqueira; R.A. Weigel; G. R. Nunes; C.S. Mori; W.R. Fernandes (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2014)
Increased oxidative stress during prolonged endurance exercises may result in muscle damage, fatigue and decreased performance. An adequate stress response during training is critical to obtain improved results and high animal welfare standards. The aim of this study was to evaluate the red blood cell haemolysate concentrations of superoxide dismutase (SOD), glutathione peroxidase (GPx), reduced glutathione (GSH) and catalase (CAT) and the plasma concentrations of malondialdehyde (MDA) from endurance horses in different distances at high speed in a tropical climate. Fifteen horses were tested; five at 160km (18.54 - 17.16km/h race speed), five at 120km (21.53 - 17km/h race speed) and five at 80km (20.06 - 18.01km/h race speed). Blood samples were collected at rest, immediately after and three hours after the horses left the final vet check and three, seven and fourteen days after the race. No significant increases (P > 0.05) in the levels of SOD, GPx, GSH, CAT or MDA were observed for any of the times or distances examined. Based on these observations, we conclude that reactive oxygen species (ROS) formation during exercise evokes specific adaptations, such as increased antioxidant/oxidative damage-repairing enzyme activity, increased resistance to oxidative stress and lower levels of oxidative damage.